Improving the Performance of the Current Cook Stove to Realize Ethiopia’s Sustainable Development Goals - Mengistu Teshome; Eshetu Getahun; Dawit Tessema Ebissa (Journal of Engineering)
Ethiopia’s Sustainable Development Goals (SDGs) can be greatly aided by improving cook stove performance because it will increase energy efficiency, lessen indoor air pollution, and reduce deforestation. This study evaluated the new stove using a comparative analysis with the current Mirt stove, considering its thermal efficiency, specific fuel consumption, cooking time, and pollution reduction. The conventional water boiling and control cooking experiments were carried out using eucalyptus wood as fuel, yielding insightful results about the new stove’s performance. Notably, the new stove’s double-wall construction and use of flue gas as an insulator resulted in notable advancements. With the new stove attaining a thermal efficiency of 28.42% as opposed to the Mirt stove’s 23.47%, there was a noticeable gain in combustion efficiency of 7.47%. Additionally, there was a 7.21% drop in the specific fuel consumption and a 5.55% rise in the firepower produced in the combustion chamber. The new stove showed a time savings of 12.15% in every injera baking activity, reducing the cooking time, which is one of the most significant results. One kilogram of injera took an average of 3.92 min to bake on the new, better stove, as opposed to 4.41 min on the Mirt stove. In addition, compared to the Mirt stove, the injera quality examination showed a 2.8% improvement in moisture content, consistency, and general sensory qualities. Apart from these improved performance gains, the new stove’s fuel savings are expected to result in a considerable reduction of greenhouse gas emissions, amounting to 0.198 t CO2/year. This highlights the wider environmental and sustainability advantages of the upgraded injera baking stove.